Armenia And Syria - What Shapes the Relations? - Mushegh Ghahriyan; Grigor Vardanyan (Banber Arevelagitut'yan Instituti, 2025)
The article discusses the major tendencies of the development of Armenian-Syrian relations during the last 30 years based on the primary sources, including the archive of the Ministry of Foreign Affairs of Armenia, other official documents, and statistical data. The research is an attempt to explain what determines the relations between the two countries and the dynamics of these relations. It represents political, economic and social factors determining the relationship between Armenia and Syria.